The use of antibacterial drugs in the treatment of coronavirus infection in children in real outpatient clinic practice - A. S. Ginzburg; A. P. Kiryutkina; N. B. Migacheva (Аллергология и Иммунология в Педиатрии, 2023)
Introduction. In light of the available data on the unjustified use of antibiotics in children with acute respiratory viral infections, the frequency of prescribing antibacterial drugs to children with a new coronavirus infection in real clinical practice is of great practical and scientific interest.The aim of the study was to study the frequency of antibiotic therapy and identify factors that increase the risk of needing antibiotics in children with coronavirus infection at the outpatient stage.Materials and methods. A retrospective cross-sectional study was conducted on the basis of children's polyclinics in Samara from November 2021 to July 2022, which included a survey of parents and an analysis of outpatient records of 100 children who were under outpatient observation and treatment for COVID-19. An analysis was made of the frequency of prescribing antibiotics to them and potential factors predisposing to their prescribing to children with COVID-19. The obtained data were subjected to statistical processing using the IBM SPSS Statistics 25 program and a comparative analysis.Results. The frequency of use of antibiotic therapy according to the results of the study was 11 % and did not exceed the Russian average data (14.3 %). When analyzing the factors influencing the doctor's decision to prescribe an antibiotic to a child with coronavirus infection, the most important were a history of recurrent respiratory infections (children from the FIC group), as well as the presence of concomitant diseases and background conditions in children, primarily chronic bronchopulmonary diseases. and nervous system.Discussion. The prescription of antibiotics for children with a new coronavirus infection at the outpatient stage remains empirical due to the limitations of the use of laboratory and instrumental methods for additional examination of the child, which objectifies the likelihood of a secondary bacterial infection. Despite this, the frequency of antibiotic use according to the results of the study was 11 % and did not exceed the Russian average data (14.3 %), as well as the average frequency of antibiotic use for acute respiratory viral infections in children in the Russian Federation (21.5-23.3 %).